2022
DOI: 10.3390/diagnostics12122992
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Is Associated with the Risk of Obstructive Sleep Apnea: A Population-Based Nationwide Cohort Study

Abstract: The association between glaucoma and the risk of obstructive sleep apnea (OSA) has not been fully evaluated. Therefore, this study aimed to investigate the prospective association between glaucoma and OSA. In total, 1437 patients with glaucoma and 5748 patients without glaucoma were enrolled after 1:4 propensity score matching using a nationwide cohort sample. We investigated OSA events during a 10-year follow-up period. Survival analysis, the log-rank test, and Cox proportional hazards regression models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“… 12 In contrast, a population-based nationwide cohort study showed no significant increase in the risk of OSA in patients with POAG. 10 A meta-analysis of OSA in patients with glaucoma confirmed that OSA is associated with a significantly increased risk of glaucoma. 48 A recently published meta-analysis suggested that OSA is associated with a higher risk of glaucoma and its subtype.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 12 In contrast, a population-based nationwide cohort study showed no significant increase in the risk of OSA in patients with POAG. 10 A meta-analysis of OSA in patients with glaucoma confirmed that OSA is associated with a significantly increased risk of glaucoma. 48 A recently published meta-analysis suggested that OSA is associated with a higher risk of glaucoma and its subtype.…”
Section: Discussionmentioning
confidence: 98%
“…[6][7][8] In contrast, patients with glaucoma are more susceptible than healthy people to sleep dysfunction such as obstructive sleep apnea (OSA), snoring, or insomnia. [9][10][11][12][13] Despite increasing evidence from observational studies suggesting a correlation between sleep behaviors and POAG, there have also been several clinical studies reporting no association between them, [14][15][16] with the existing literature on the subject being inconclusive and debatable. Additionally, whether demographics, socioeconomic status, and comorbidities are potential confounding factors in this relationship remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, cancer patients have a higher risk of stroke compared to the general population, and cancer-related stroke is a major factor in lowering the survival rate of cancer patients [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Some systematic reviews have also described that the relative risk of stroke is higher in cancer survivors than in the cancer-free population over an unspecified follow-up period [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies performed a validation analysis on the cohort profile and showed a similar prevalence of major diseases every year [ 17 , 18 ]. Moreover, this cohort dataset has been widely used to elucidate the association between two certain diseases [ 19 , 20 , 21 , 22 ]. This indicates that the cohort dataset is highly reliable.…”
Section: Methodsmentioning
confidence: 99%
“…8) Recently, the applicability of the STOP-Bang score has expanded, not only to assess OSA risk but also to gauge the severity of OSA; however, further research is required. Although some previous studies have explored the association between glaucoma and OSA, 9,10) only a few have examined the risk of OSA in glaucoma patients using the STOP-Bang score. 11,12) In particular, only a few studies have investigated the association between OSA risk and severity using the STOP-Bang score and the risk of glaucoma or increased IOP using Korean national data.…”
Section: Introductionmentioning
confidence: 99%